Research on the influence of the dynamic viscosity of raw material fermented in a biogas reactor on heat distribution - Spodoba, М. О.; Spodoba, О. О. (Energy and Automation, 2025)
Biogas plants are becoming increasingly popular among industry and domestic consumers. This has led to increased interest in conducting research to increase the profitability of such plants. First of all, researchers are focusing their attention on creating systems that will satisfy the conditions for anaerobic digestion and at the same time consume a minimum amount of electrical energy for mixing and heating the substance. After all, for fermentation, raw materials with different physicochemical composition are used, which significantly affects energy costs. The aim of the work is to study the influence of the dynamic viscosity of the raw materials fermented in a biogas reactor on the change in the Reynolds criterion and heat transfer coefficients from the rotating heater to the raw materials. The article presents a mathematical model for conducting theoretical studies. The work considers the change in the dynamic viscosity of the substrate in the range from 0.01 to 0.1 Pa·s. It was found that when the dynamic viscosity of the raw material changes in the range from 0.01 to 0.1 Pa·s, the Reynolds criterion and heat transfer coefficients change according to an exponential law, which is confirmed by the graphical dependencies obtained during the research and presented in this work. The results obtained will further allow us to establish a rational rotation frequency of the mixing device combined with a heating device, taking into account the change in the dynamic viscosity of the raw material, to create and maintain a favorable microclimate for the anaerobic process with the maximum possible formation of biogas.Key words: reynolds criterion, energy consumption, heat transfer coefficient, dynamic viscosity of raw materials, fermentation, heat transfer coefficient, mixing